TRAINING OF PH.D. STUDENTS TO TAKE INTO ACCOUNT CULTURAL DIFFERENCES WHEN COMMUNICATING IN A FOREIGN LANGUAGE ENVIRONMENT (Innovative professional education, 2022)
When preparing applicants for the scientific degree Ph.D. "015 – Professional Education" to take into account cultural differences when communicating in a foreign language environment, it is necessary to take into account the differences in behavior that are specific to different cultures. The growth of intercultural communication interaction and the spread of English in the international educational environment contributes to the importance of taking into account the cultural differences of interlocutors. To understand the specifics of the behavior ofrepresentatives of other countries can be based on the use of indices of the Hofstede model.
Keywords: cultural differences, public-private partnership (PPP), foreign language environment, applicant for a scientific degree, Hofstede model indices.